Dental caries risk index - Vielka González Ferrer; Milagros Alegret Rodríguez; Judith Martínez Abreu; Yainedy González Ferrer (Editorial Ciencias Médicas, 2017)
Introduction: dental caries risk indices make it possible to focus on preventive actions and optimize health resources, leading to better results in dental care. Objective: evaluate the discriminating capacity of a dental caries risk index. Methods: the study was conducted in two stages, corresponding to development and validation of the index. These took place during school years 2012-2013 and 2013-2014, respectively. The first stage was a case-control study with children aged 6-12 from three elementary schools in Santa Clara, Cuba. At the outset, the presence of caries was discarded and information was collected about a number of variables. Ten months later the 120 children with detected caries were selected as cases, and 240 controls were randomly chosen from among the remaining children. An index was developed applying a procedure based on Cramér's V and a caries prediction model based on logistic regression. The second stage was a cross-sectional study with 360 children to validate the index and contrast it with the prediction model on the basis of the area under the curve, recipient's operative characteristics, and other measures estimated with 2 x 2 tables. Results: the index showed sensitivity, specificity and validity values of 87.5 %, 82.5 % y 84.2 % respectively. The regression model obtained percentage values of 80.8 %, 81.3 % and 81.1 %. The area under the curve was 0.889 for the former and 0.870 for the latter. Conclusions: results attest to the validity of the index obtained through Cramér's V values as an important tool to identify the risk for, and therefore the prevention and control of dental caries in children aged 6-12 resident in Santa Clara.